SMARTPLS FOR THE ROLE 0F MANAGEMENT ACCOUNTING SYSTEM TO MANAGERIAL PERFORMANCE WITH TASK UNCERTAINTY AS A MODERATING VARIABLE - David Efendi, Imam Ghozali (International Journal of Advanced Science and Technology, 2020)
The point of this exam became to investigate the impact the board bookkeeping framework to challenge uncertaninty and administrative execution. Records from 5861 administrator agreeable chief have been to check the executives bookkeeping framework, task vulnerability and administrative execution. Statistics had been dissected with SPSS and Smartpls. SPSS is carried out for non response inclination and unmistakable size. SMartPLS is applied to hyphothesis test. Reseacrh coming across, the board bookkeeping framework absolutely affects administrative execution and project vulnerability reinforces the board bookkeeping framework influencing administrative execution